2017
DOI: 10.1021/acs.jpca.7b08385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Electron Transfer in the Reactions of Hydrated Monovalent First-Row Transition-Metal Ions M(H2O)n+, M = V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, n < 40, toward 1-Iodopropane

Abstract: Hydrated metal ions in the gas phase serve as model systems to investigate the impact of hydration on the chemistry of monovalent transition-metal centers. As a prototypical organometallic reaction involving electron transfer, the reactions of M(HO), M = V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, n < 40, with CHI are studied by Fourier transform ion cyclotron resonance mass spectrometry. While no reaction was observed for vanadium, three different reactions were observed with the other metals, two of them involving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…47 With 1-iodopropane, Zn + (H 2 O) n reacts efficiently to ZnI + (H 2 O) m , again with oxidation of the Zn centre. 48 These studies showed that hydrated monovalent zinc ions can be oxidized by suitable reactants, but the details of the reactions and their cluster size-dependence can be quite complex. The question arises whether hydrated electrons are formed in sufficiently large clusters, similar to Mg + (H 2 O) n , 21 however an insertion to form HZnOH + does not seem plausible, given the lack of H/D exchange in the D 2 O experiment.…”
Section: Introductionmentioning
confidence: 99%
“…47 With 1-iodopropane, Zn + (H 2 O) n reacts efficiently to ZnI + (H 2 O) m , again with oxidation of the Zn centre. 48 These studies showed that hydrated monovalent zinc ions can be oxidized by suitable reactants, but the details of the reactions and their cluster size-dependence can be quite complex. The question arises whether hydrated electrons are formed in sufficiently large clusters, similar to Mg + (H 2 O) n , 21 however an insertion to form HZnOH + does not seem plausible, given the lack of H/D exchange in the D 2 O experiment.…”
Section: Introductionmentioning
confidence: 99%
“…32 They also explained the switch off for the hydrogen loss process for larger clusters due to the barrier increase when the solvated electron moves beyond the third solvation shell. 15 Our group has a long history in studying the reactivity of hydrated metal ions, 13,16,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) which is well suited for this task as it allows highest mass resolution coupled with long storage times to allow multiple collisions with reactant gases. In the present study, we couple the mass spectrometer with a tunable optical parametric oscillator (OPO)/amplifier system to conduct photodissociation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Metal cluster stability and reactivity are often determined by gas-phase reactions. , For example, the reactivity of Al cluster anions with water demonstrated that complementary active sites account for the size-selective reactivity, unveiling dependence on geometric rather than electronic shell structure . Also, extensive studies have revealed the diverse reactivities of transition metal ions and clusters in a variety of conditions, motivated by the application potentials in catalysis, battery cathodes, and magnetic materials. , Among them, the studies on the size-dependent reactivity of vanadium clusters with CO, NO, O 2 , D 2 , N 2 , C x H x , alcohols, and many other species have been conducted, , allowing us to quantitatively estimate the reaction probability and catalytic behavior. In particular, several studies have revealed the geometric structures, electronic properties, and kinetics involved in the novel coordination chemistry of vanadium cations with water, as well as electronic properties of hydrated V n clusters .…”
mentioning
confidence: 99%
“…Also, extensive studies have revealed the diverse reactivities of transition metal ions and clusters in a variety of conditions, motivated by the application potentials in catalysis, battery cathodes, and magnetic materials. , Among them, the studies on the size-dependent reactivity of vanadium clusters with CO, NO, O 2 , D 2 , N 2 , C x H x , alcohols, and many other species have been conducted, , allowing us to quantitatively estimate the reaction probability and catalytic behavior. In particular, several studies have revealed the geometric structures, electronic properties, and kinetics involved in the novel coordination chemistry of vanadium cations with water, as well as electronic properties of hydrated V n clusters . Recently, we studied the reactions of ionic vanadium clusters and found significant H 2 release from single H 2 O molecules in reacting with cationic V n + , revealing decisive advantages of vanadium clusters (rather than single atoms) for hydrogen evolution reaction (HER) from water.…”
mentioning
confidence: 99%